Starting Afresh : Freedom Dues vs Reality in 17th Century Chesapeake - Elodie Peyrol-Kleiber (Cahiers du MIMMOC)
When servants would sign a contract, they knew it was for a determined span of time. However, what was on the paper was not an automatic reflection of the 17th century reality, especially in a foreign land where everything had to be done, and where the mortality rate and dangers were high. Therefore, contracting an indenture often meant not recovering one’s freedom. In the case where a servant would survive his time of servitude, he had the right to claim freedom dues on the part of his master. Those were meant to help him settle as a free colonist, buying land, raising cattle and planting tobacco. This article focuses on the reality of the freedom dues, landownership and opportunities after the end of an indenture by contrasting what was on the paper with the real experiences of this class of often-forgotten commoners, however essential they were to feed the hungry stomach of the tobacco market.